Kajian Produksi Es Krim Probiotik Dengan Penambahan Bakteri Asam Laktat Enkapsulasi - Lela Natalia; Fajar Restuhadi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to study the viability of lactic acid bacteria (Lactobacillus acidophilus) encapsulation in the ice cream with the conditions of low temperature and pH 2. The research was carried out experimentally by using Completely Randomized Design (CRD) with four treatments and four replications, namely: A0, A1, A2, and A3, respectively for alginate 0% (control), alginate 3 %, alginate 4 % and alginate 5 % (v/v) culture of Lactobacillus acidophilus. Data were statistically analyzed using Analysis of Variance (ANOVA) followed by DNMRT test at the 5% level. Results of this study indicated that the alginate concentration had a significant effect (P<0.05) on the survival of Lactobacillus acidophilus at 0 hour storage, freezing storage for 48 hours, pH 2 and texture of ice cream. The treatment of A3 (Alginate 5 %) resulted in viability Lactobacillus acidophilus on storage 0 hours (99.02%), frozen storage for 48 hours (79.32 %), and the condition of pH 2 (37.33%) was relatively better than others treatments. The best Sensory Evaluation obtained on treatment A0 where the ice cream was no sensation of gel beads and very soft texture. The whole assessment of it was on A0 treatment. Keywords: probiotic, ice cream, encapsulation, alginate